2019
DOI: 10.1093/ecco-jcc/jjz064
|View full text |Cite
|
Sign up to set email alerts
|

Butyrate Does Not Protect Against Inflammation-induced Loss of Epithelial Barrier Function and Cytokine Production in Primary Cell Monolayers From Patients With Ulcerative Colitis

Abstract: Background and Aims In vitro studies using immortalised cancer cell lines showed that butyrate has an overall positive effect on epithelial barrier integrity, but the physiological relevance of cancer cell lines is limited. We developed epithelial monolayers from human tissue samples of patients with ulcerative colitis [UC] to assess the effect of butyrate on epithelial barrier function. Methods A protocol to establish monola… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
40
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 56 publications
(46 citation statements)
references
References 61 publications
4
40
1
Order By: Relevance
“…Ours is the first study to compare the intrinsic ability of human epithelial organoids from UC and CD patients to uptake, metabolize, and respond to butyrate, along with the complex SCFA mixtures extracted from fecal samples. We clearly show that organoids from noninflamed IBD mucosa respond to butyrate similarly to controls, which is consistent with recent observations by Vancamelbeke et al, 42 who found no differences in the response of control and UC cultures to butyrate, alone or in combination with TNFɑ/IFNγ. On the other hand, we confirmed in both ex vivo epithelial cultures and whole mucosal samples that the inflammatory milieu, in particular the presence of TNFɑ, does impact butyrate uptake and oxidation.…”
Section: Discussionsupporting
confidence: 93%
“…Ours is the first study to compare the intrinsic ability of human epithelial organoids from UC and CD patients to uptake, metabolize, and respond to butyrate, along with the complex SCFA mixtures extracted from fecal samples. We clearly show that organoids from noninflamed IBD mucosa respond to butyrate similarly to controls, which is consistent with recent observations by Vancamelbeke et al, 42 who found no differences in the response of control and UC cultures to butyrate, alone or in combination with TNFɑ/IFNγ. On the other hand, we confirmed in both ex vivo epithelial cultures and whole mucosal samples that the inflammatory milieu, in particular the presence of TNFɑ, does impact butyrate uptake and oxidation.…”
Section: Discussionsupporting
confidence: 93%
“…This finding is concordant with recent publications in which butyrate or butyrate-producing fermentable fiber are found to exacerbate the severity of experimental colitis. 39,[50][51][52][53] These observations also coincide with current practices to exclude fermentable oligosaccharides, disaccharides, monosaccharides, and polyols from the diet of IBD patients. 54,55 Caloric intake regulates tissue homeostasis and health.…”
Section: Discussionsupporting
confidence: 62%
“…have been associated with the production of butyrate, which is the major energy source of colonic epithelial tissue and may be involved in immune regulation and intestinal-barrier function [37,38,39,40]. In contrast, recent studies [41,42] have shown that butyrate is not universally beneficial for intestinal health. Lachnospiraceae and Ruminococcaceae differ with respect to their average numbers of carbohydrate-active genes and gene families, particularly glycoside hydrolases and carbohydrate-binding modules, which are more abundant and more diverse in Lachnospiraceae and Ruminococcaceae [43].…”
Section: Discussionmentioning
confidence: 99%